2015
DOI: 10.1542/peds.2015-0224
|View full text |Cite
|
Sign up to set email alerts
|

Incidence, Trends, and Survival of Children With Embryonal Tumors

Abstract: BACKGROUND: Central nervous system (CNS) and non-CNS embryonal tumors occur principally in children and are rarely seen in adults. The incidence rates for rare entities such as atypical teratoid/rhabdoid tumors (AT/RT) or primitive neuroectodermal tumors in the CNS are rarely published. Incidence rates for certain subgroups, such as hepatoblastomas, have been increasing in some countries.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
44
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(56 citation statements)
references
References 51 publications
11
44
0
1
Order By: Relevance
“…In our study we did not find a difference in survival between the TYA age group and children aged 5-9 years. We did however observe a doubling of the risk of death for those aged under 5 years, consistent with other studies (3,5,(15)(16)(17)(18)(19)31) due to treatment strategies for infants and young children that defer or avoid radiation (7).…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…In our study we did not find a difference in survival between the TYA age group and children aged 5-9 years. We did however observe a doubling of the risk of death for those aged under 5 years, consistent with other studies (3,5,(15)(16)(17)(18)(19)31) due to treatment strategies for infants and young children that defer or avoid radiation (7).…”
Section: Discussionsupporting
confidence: 91%
“…Central nervous system (CNS) tumours are the second most common site of neoplasms diagnosed in children, accounting for approximately one quarter of all childhood cancers (0-14 years), (1) and 14% of tumours diagnosed in teenagers and young adults (TYA) (15)(16)(17)(18)(19)(20)(21)(22)(23)(24) years) (2). They are the most common cause of cancer related death in children and TYA (1,2).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…This is in contrast with other studies, which have identified the male sex as a risk factor for neuroblastoma. 46,47 Childhood carcinomas are rare. Consequently, they occurred infrequently in children with cancer who were treated at the NCI.…”
Section: Gender Percentage (%)mentioning
confidence: 99%